Asia bond monitor (Asian Development Bank, Regional Economic Monitoring Unit, 2004)
The Asia Bond Monitor (ABM) reviews the development of Asian local currency bond markets. It examines market size and composition, market liquidity, investor profile, and returns and volatility. Recent policy reforms and challenges facing these markets are also highlighted.